Healthy Eating for Elders: Smart Snacking - Jennifer Hillan (EDIS)
Snacking can be good for you! Healthy snacks provide vitamins and minerals that may be lacking from your main meals. Keep these smart snacking tips in mind the next time you have a “snack attack.” This is document FCS 8698-ENG, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: February 2005.